Results of experimental electromagnetic studies of the Crimean region - T. K. Burakhovich; A. M. Kushnir; I. Yu. Nikolaev; E. M. Sheremet; B. I. Shirkov (Геофизический журнал, 2016)
Spatial-temporal pattern of distribution of geomagnetic variations and the electric field on the Earth’s surface was obtained as a result of the modern experimental observations conducted in 2007—2013 along 9 profiles (48 points) by the methods of magnetotelluric sounding (MTS) and magnetovariation profiling (MVP). These profiles cross various geological structures of the Crimean region. It is possible to estimate the value of the electrical conductivity and vertical and horizontal geoelectric structure. The processing of these data is done using modern software system PRC_MTMV (author Varentsov Iv. M.) that provides the common noise-protected evaluation of the impedance, tipper, horizontal magnetovariation response according to the synchronous MT/MV records.